Hopper's destiny - Fiedler, Lisa (Fiedler, Lisa. Mouseheart, 2015)
A brave pet shop mouse named Hopper attempts to rebuild a fallen empire in the underground rat civilization of Atlantia, located in the subway tunnels of Brooklyn, while Queen Felina and her band of street cats declare open season on the rodents.